Empowerment of youth care about reproductive health in the covid-19 pandemic era - Terry Y.R. Pristya; Chahya Kharin Herbawani; Ulya Qoulan Karima; Arnur Oktafiyanti; Nadia Ramadhanty (Community Empowerment, 2021)
Adolescence is a transition period of human life. Various problems were experienced at that time, especially regarding reproductive health. During the COVID-19 pandemic, youth groups and posyandu activities were stopped. There were many activities previously made by the youth, including joint sports, joint dawn, and Friday night recitations. This shows that there are no activities related to reproductive health. Therefore, the purpose of this community service is to form youth care about reproductive health. The service activities are carried out through 6 stages, starting with discussions with partners about the importance of youth activities in the Covid-19 pandemic, and continued by forming a youth care team. The community service provided knowledge about adolescent reproductive health, socialization of 3 BKKBN modules, training in making handbooks, and the election of ambassadors for adolescent reproductive health. The results are the formation of adolescents who care about reproductive health, increased knowledge, and reproductive health handbooks.